Microwaves Scattering by Underdense Inhomogeneous Plasma Column - 张林 欧阳吉庭 (Plasma science & technology, 2016)
The scattering characteristics of microwaves （MWs） by an underdense inhomoge- neous plasma column have been investigated. The plasma column is generated by hollow cathode discharge （HCD） in a glass tube filled with low pressure argon. The plasma density in the column can be varied by adjusting the discharge current. The scattering power of X-band MWs by the column is measured at different discharge currents and receiving angles. The results show that the column can affect the properties of scattering wave significantly regardless of its plasma frequency much lower than the incident wave frequency. The power peak of the scattering wave shifts away from 0° to about ±15° direction. The finite-different time-domain （FDTD） method is employed to analyze the wave scattering by plasma column with different electron density distributions. The reflected MW power from a metal plate located behind the column is also measured to investi- gate the scattering effect on reducing MW refiectivity of a metal target. This study is expected to deepen the understanding of plasma-electromagnetic wave interaction and expand the applications concerning plasma antenna and plasma stealth.